2000
DOI: 10.1590/s0103-84782000000200019
|View full text |Cite
|
Sign up to set email alerts
|

Motilidade espermática e integridade acrossomal em doses de sêmen suíno refrigeradas e inoculadas com Esecherichia coli e Staphylococcus aureus

Abstract: RESUMO Foram utilizados 12 ejaculados, coletados de maneira asséptica, distribuídos em sete tratamentos, sendo um grupo controle e os demais inoculados com três diferentes concentra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
2
Order By: Relevance
“…Furthermore, when bacteria are introduced in a new environment, which occurs through semen dilution, they require a certain time for recovery and adaptation to metabolize the substrates present in the extender (ALTHOUSE, 2008). Bacteria can have difficulties in adapting and growing in the new environment (BENNEMANN et al, 2000) and, if they are sensitive to antimicrobial agents present in the extender, the contamination will probably be reduced. However, if the source of contamination is the extender itself, bacterial growth can be facilitated, as the bacteria are already fully adapted to the environment with an appropriate temperature and a high amount of substrate, in addition to the possible development of antimicrobial resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when bacteria are introduced in a new environment, which occurs through semen dilution, they require a certain time for recovery and adaptation to metabolize the substrates present in the extender (ALTHOUSE, 2008). Bacteria can have difficulties in adapting and growing in the new environment (BENNEMANN et al, 2000) and, if they are sensitive to antimicrobial agents present in the extender, the contamination will probably be reduced. However, if the source of contamination is the extender itself, bacterial growth can be facilitated, as the bacteria are already fully adapted to the environment with an appropriate temperature and a high amount of substrate, in addition to the possible development of antimicrobial resistance.…”
Section: Resultsmentioning
confidence: 99%
“…By binding to spermatozoa, bacteria cause ultrastructural lesions in the plasma membrane (DIEMER et al, 1996), and the acrosomal integrity is compromised in most agglutinated sperm samples (KUSTER; ALTHOUSE, 1997). Bennemann et al (2000) studied the effect of S. aureus and E. coli at different concentrations in semen doses on acrosome alterations and observed that after 48 h of storage E. coli (5 x 10 7 CFU mL -1 ) caused a significant increase in abnormal acrosomes. Apparently, the time of onset of sperm changes and the magnitude of changes in pH, motility and acrosome integrity are dependent on the bacterial genera and their concentration in the semen doses.…”
mentioning
confidence: 99%
“…A mão de obra qualificada é de grande importância, pois a manutenção de pessoas treinadas é fundamental para a qualidade do trabalho (Bortolozzo & Wentz, 2005). O resultado encontrado de baixa contaminação bacteriana nas doses espermáticas na central de inseminação artificial 2 corresponde com o descrito por Bennemann et al (2000) relatam que ao coletar ejaculados com absolutos cuidados higiênicos, sob condições experimentais, não observaram crescimento bacteriano até 48 horas de incubação no sêmen in natura.…”
Section: Todas As Centrais De Inseminaçãounclassified
“…Preconiza-se que entre a coleta e o armazenamento das doses haja uma queda gradual e contínua de temperatura até alcançar o ponto de armazenamento entre 15 e 18º C de temperatura (Bortolozzo & Wentz, 2005). No entanto, essa temperatura Batista et al (2012) Archives of Veterinary Science, v.17, n. Bennemann et al, (2000) eram livres de contaminação bacteriana e a inoculação das bactérias testadas foi realizado laboratorialmente. No projeto em estudo as análises foram realizadas de amostras de sêmen coletadas diretamente das centrais de inseminação artificial e em muitas amostras analisadas havia diferentes gêneros bacterianos na mesma amostra e sabe-se que bactérias produzem metabólitos que podem ser tóxicos para outros microrganismos (Tortora et al, 2000).…”
Section: Todas As Centrais De Inseminaçãounclassified